Effect of Sublethal Dose of Ethion on Selected Biochemical Parameters in the Pancreas of Albino Rat - Devi, P. Sachi; Kumar , D. Veera Nagendra (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Ethion is an organophosphorus (OP) insecticide that was specifically developed as an effective solution for controlling insects, mites, and eggs on both plants and animals. Its primary application is as an insecticide, acaricide, and ovicide. The purpose of this study was to examine the impact of ethion on protein metabolism in the pancreas of Albino rats by assessing its sublethal effects. During the course of the experiment, adult male Albino rats of the Wistar strain were given ethion orally. The dosage administered was 1/5th of the LD50 value, which equates to 42mg/kg of their body weight. The rats were subjected to this treatment for a duration of 30 days, with a 48-hour interval between each administration. The rats were randomly divided into four groups for the experiment. The first group of rats served as the control, receiving no ethion treatment. The second group of animals was treated with ethion for a duration of 10 days. The third and fourth groups of rats were administered ethion for 20 and 30 days, respectively. In groups administered with ethion, the levels of total proteins exhibited a decrease. However, all the parameters analyzed in this study demonstrated an overall increase. Notably, the increase observed in the 30-day administered group was more prominent compared to the groups administered for 20 and 10 days. Ethion exposure led to severe alterations in all the parameters studied in Albino rats during the present investigation. Histopathological studies were conducted to evaluate the extent of damage caused. Examination of the pancreas in Albino rats exposed to Ethion revealed various histological observations. These included Cloudy Swelling with Granulated Cytoplasm (CSGC), Denatured nucleus (DN), Hemorrhage (H), and Congestion (C). The study findings indicate that the administration of Ethion has negative consequences on pancreatic functions, resulting in impairments to its normal physiological functioning. The study suggests that Ethion's toxic impact is manifested by disrupting various aspects of protein metabolism within the pancreas of Albino rats.